2019
DOI: 10.1002/jez.b.22861
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of key lipases during the larval development of walking catfish (Clarias magur)

Abstract: The study was conducted to investigate the expression and activity of key lipolytic enzymes during the ontogenetic development of Clarias magur. After partial characterization, the messenger RNA (mRNA) expression analysis of lipoprotein lipase (LPL), pancreatic triacylglycerol lipase (PL), and bile salt-activated lipase (BAL) genes along with the specific lipase activity were performed in larvae from Day 1 after hatching till 34-day posthatch (dph). Heterogeneous patterns of mRNA expression were shown by the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The temporal variation in expression levels of lipolytic genes was evaluated, and it was found that only LPL displayed significant difference in the relative mRNA levels. The significant decrease in the LPL gene expression can be correlated with the results of our previous study (Mir et al, 2019), where it showed a declining trend after 16 dph. Whether the effect on the lipolytic gene expression was due to age or difference in dietary protein level could not be differentiated as the three time points represent the samples fed with different protein levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The temporal variation in expression levels of lipolytic genes was evaluated, and it was found that only LPL displayed significant difference in the relative mRNA levels. The significant decrease in the LPL gene expression can be correlated with the results of our previous study (Mir et al, 2019), where it showed a declining trend after 16 dph. Whether the effect on the lipolytic gene expression was due to age or difference in dietary protein level could not be differentiated as the three time points represent the samples fed with different protein levels.…”
Section: Discussionsupporting
confidence: 88%
“…During the rearing period, different water quality parameters like dissolved oxygen, temperature, and pH were observed to be in the optimum ranges of 6-8 mg L −1 , 28-30 • C and 7.8-8.2, respectively. The experiment conducted from the 14 dph stage was based on the inference from our previous study (Mir et al, 2019), where the C. magur was found to efficiently utilize dietary lipids from 13 dph onward. Nine experimental diets were prepared with combination of three lipids (8, 10, and 12%) and three protein levels (55, 50, and 45%).…”
Section: Experimental Designmentioning
confidence: 99%
“…The alignment of RpL36 amino acid sequences was done by DNAMAN 6.0. The neighbor‐joining (NJ) tree of the RpL36 of D. melanogaster with other species was constructed using MEGA 7.0 (Mir et al, 2019), and bootstrap analysis was performed using 1000 replicates.…”
Section: Methodsmentioning
confidence: 99%